Selection of reference genes for expression analysis in Diuraphis noxia (Hemiptera: Aphididae) fed on resistant and susceptible wheat plants - Sinha, Deepak K.; Smith, C. Michael (My University, 2014)
The Russian wheat aphid (RWA), Diuraphis noxia Kurdjumov, is a major global pest of wheat and barley production that causes enormous economic damage. Few studies have been conducted to explore and decipher the molecular basis of RWA strategies to evade plant defense mechanisms. Gene expression studies of RWA in response to wheat genotypes carrying different RWA resistance genes have been initiated in our group; however, a secure and accurate understanding of RWA gene expression is dependent on identification of suitable reference genes. This study analyzed expression profiles of five potential reference genes selected and sequenced during RNA sequencing experiments. The expression of genes coding for actin and ribosomal protein L27 was comparatively less variable in RWA fed on different wheat hosts. Results of geNorm, NormFinder, and BestKeeper expression analyses support the use of actin and ribosomal protein L27 in RT-qPCR studies of RWA gene expression in studies involving RWA-wheat interactions.
Citation: Sinha, D.K. & Smith, C.M. Selection of Reference Genes for Expression Analysis in Diuraphis noxia (Hemiptera: Aphididae) Fed on Resistant and Susceptible Wheat Plants. Sci. Rep. 4, 5059; DOI:10.1038/srep05059 (2014).
Keywords: Russian wheat aphid; Diuraphis noxia Kurdjumov; Gene expression; Wheat